2018
DOI: 10.1504/ijhrdm.2018.10014185
|View full text |Cite
|
Sign up to set email alerts
|

Through the glass ceiling: is mentoring the way forward?

Abstract: Over the past 30 years, the term the 'glass ceiling' has come to be known as a metaphor for vertical segregation, symbolising an invisible barrier that prevents women from progressing in their careers. Increasingly women are found in higher level positions and mentoring has often been touted as an important way to help women break through the glass ceiling. This paper explores the continued relevance of the glass ceiling and the use of mentoring programs as a means to help women to overcome it. The findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 148 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…The equality and diversity and inclusion of women in the built environment may encourage more females to enter the industry. However, it is being reported that the dominance of men in the industry puts off potential work candidates in the industry because of a lack of females to look up to and also to mentor them during their careers (Noe, 1988;Caprice et al, 2018). Also, the underrepresentation of women is attributed to cultural and structural problems as well as the pre-conceived nature that females are predisposed to work (Soo-Cheen, et al, 2020).…”
Section: Proof Of the Existence Of Gender Imbalance In The Real Estat...mentioning
confidence: 99%
“…The equality and diversity and inclusion of women in the built environment may encourage more females to enter the industry. However, it is being reported that the dominance of men in the industry puts off potential work candidates in the industry because of a lack of females to look up to and also to mentor them during their careers (Noe, 1988;Caprice et al, 2018). Also, the underrepresentation of women is attributed to cultural and structural problems as well as the pre-conceived nature that females are predisposed to work (Soo-Cheen, et al, 2020).…”
Section: Proof Of the Existence Of Gender Imbalance In The Real Estat...mentioning
confidence: 99%